2005
DOI: 10.1136/bmj.38628.466898.55
|View full text |Cite
|
Sign up to set email alerts
|

Systematic review of misdiagnosis of conversion symptoms and “hysteria”

Abstract: Objective Paralysis, seizures, and sensory symptoms that are unexplained by organic disease are commonly referred to as "conversion" symptoms. Some patients who receive this diagnosis subsequently turn out to have a disease that explains their initial presentation. We aimed to determine how frequently this misdiagnosis occurs, and whether it has become less common since the widespread availability of brain imaging. Design Systematic review. Data sources Medline, Embase, PsycINFO, Cinahl databases, and searches… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
150
1
13

Year Published

2007
2007
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 298 publications
(170 citation statements)
references
References 44 publications
6
150
1
13
Order By: Relevance
“…Seis meses após a primeira consulta, apenas em 3% dos pacientes se chegou a um diagnóstico orgânico, valor que está de acordo com Stone et al 23 , que, numa revisão sistemática dos sintomas de conversão (paralisias, convulsões e cegueira), encontraram uma redução progressiva do número de erros até a década de 1970, para posteriormente estabilizar nos 4%.…”
Section: Discussionunclassified
“…Seis meses após a primeira consulta, apenas em 3% dos pacientes se chegou a um diagnóstico orgânico, valor que está de acordo com Stone et al 23 , que, numa revisão sistemática dos sintomas de conversão (paralisias, convulsões e cegueira), encontraram uma redução progressiva do número de erros até a década de 1970, para posteriormente estabilizar nos 4%.…”
Section: Discussionunclassified
“…However, follow-up studies done after 1970 have, on average, reported a significantly lower rate of mis diagnosis of conversion symptoms, namely in the order of 0.4%-4%. 15,16 This difference may be explained by improvements in the quality of the follow-up studies and, to a lesser extent, the advances made in neuroimaging techniques.…”
Section: Diagnostic Accuracymentioning
confidence: 99%
“…Todavia, estudos mais recentes demonstram que a taxa de re-diagnóstico diminuiu muito, atribuindo tal mudança ao desenvolvimento de métodos diagnósticos mais apurados (Mace e Trimble, 1996;Binzer e Kullgren, 1998;Crimlisk et al, 1998). Outra explicação para a redução de erros diagnósticos observada após a década de 1970 é a melhoria na qualidade desses estudos, já que os anteriores apresentavam importantes falhas metodológicas (Stone et al, 2005).…”
Section: Introductionunclassified